Handbook of research on digital crime, cyberspace security, and information assurance - Cruz-Cunha, Maria Manuela, 1964-; Portela, Irene Maria, 1965- (Hershey, PA : Information Science Reference, 2015)
'This book combines the most recent developments in data protection and information communication technology (ICT) law with research surrounding current criminal behaviors in the digital sphere'--
Includes bibliographical references (pages 533-598) and index.
Keywords: Computer crimes; Computer security; Computer networks -- Security measures; Data protection; Information technology